Probable primary polydipsia in a domestic shorthair cat. Issue 2 (9th November 2015) - Long, Charles Tyler; Williams, Morika; Savage, Mason; Fogle, Jonathan; Meeker, Rick; Hudson, Lola
Case summary: A 10-month-old neutered male domestic shorthair cat presented with a 4 month history of polyuria and polydipsia. After a thorough diagnostic work-up the only abnormal findings were hyposthenuria and an elevated random plasma osmolality level. Trial therapy with the oral and ophthalmic forms of desmopressin failed to concentrate urine. A modified water deprivation test confirmed the ability to concentrate urine above a urine specific gravity (USG) of 1.035. After transitioning the cat to a higher sodium diet and instituting several enrichment changes to the cat's environment, average water consumption and urine output levels decreased to almost normal levels and USG increased from 1.006 to 1.022. These findings provide strong evidence that primary polydipsia was the underlying etiology of the cat's condition. Relevance and novel information: This case report exemplifies the challenges faced when a cat presents for polyuria and polydipsia without an obvious cause identified on routine diagnostics. To our knowledge, this is the first report of primary polydipsia in a cat.